Optimization of long cycle emission reduction paths for new-type power system considering electric-thermal coupling - Meng, Xiangfei; Zhao, Long; Chen, Bo; Tian, Xin; Wang, Lei; Liu, Nian (Frontiers in Energy Research, 2024)
The carbon factor is the core driving force behind the low-carbon transformation of the power system. The study of Emission Reduction Paths (ERPs) has become a key issue for the New-type Power System to achieve clean and low-carbon goals. In order to measure the relationship between ERP and the economy, this paper considers the retirement requirements of coal-fired power units and emission reduction requirements on a long cycle planning scale, and constructs a multi-scenario planning model that considers electric-thermal coupling, enabling the determination of installed capacity for power and heat sources each year. The effectiveness of the proposed model was verified using an improved IEEE-39 bus power system. A case study was conducted to analyze the economic performance of the system based on the selected ERP set. The results showed that under the rear acceleration’s ERP, the system could achieve optimal economic performance based on the selected ERP set.